Harmony and Aversion in the Face of a Pandemic. (12th March 2022) - Hitokoto, Hidefumi; Adeclas, Joane
Abstract: While the survival function of culture against infectious disease has been investigated, little is known about its psychological processes under the real‐world threat of infection. Here, we compare the subjective COVID‐19‐related symptoms of Japanese and French adults during the spring of 2021. We tested two regression models describing the downregulation of symptoms by germ aversion, and by interdependent happiness, together with relational mobility and demographics. We regard germ aversion as an individualized fending‐off process marked by discomfort with the general other in the face of possible infection. We regard interdependent happiness as a relational safeguarding process against possible infection. Results suggest that the effect of germ aversion differed across nations, negatively explaining symptoms in Japan but not in France, and that the effect of interdependent happiness was shared. A possible psychological mechanism whereby collectivist culture suppresses infection in the face of the pandemic is discussed.